Genome-wide analysis of Excretory/Secretory proteins in root-knot nematode, Meloidogyne incognita provides potential targets for parasite control. (April 2017) - Gahoi, Shachi; Gautam, Budhayash
Graphical abstract: Highlights: This paper provides the first ever genome analysis of secretory proteins in root-knot nematode, M. incognita which infects the roots of wide variety of cultivated plants and cause significant yield loss annually. In this study, we predicted and functionally annotated the 1889 secretory proteins in M. incognita genome using integration of several bioinformatics tools. Of these 1889 ES proteins, 473(25%) had orthologues in free living nematode Caenorhabditis elegans, 825(67.8%) in parasitic nematodes whereas 561 (29.7%) appeared to be novel and M. incognita specific molecules. We found 17 secretory proteins homologous to C. elegans RNAi phenotypes, possibly linked to survival of the M. incognita and could represent attractive targets for parasite control. Abstract: The root-knot nematode, Meloidogyne incognita causes significant damage to various economically important crops. Infection is associated with secretion of effector proteins into host cytoplasm and interference with host innate immunity. To combat this infection, the identification and functional annotations of Excretory/Secretory (ES) proteins serve as a key to produce durable control measures. The identification of ES proteins through experimental methods are expensive and time consuming while bioinformatics approaches are cost-effective by prioritizing the experimental analysis of potential drug targets for parasitic diseases. In this study, we predicted and functionally annotated the 1889 ES proteins in M. incognita genome using integration of several bioinformatics tools. Of these 1889 ES proteins, 473 (25%) had orthologues in free living nematode Caenorhabditis elegans, 825(67.8%) in parasitic nematodes whereas 561 (29.7%) appeared to be novel and M. incognita specific molecules. Of the C. elegans homologues, 17 ES proteins had "loss of function phenotype" by RNA interference and could represent potential drug targets for parasite intervention and control. We could functionally annotate 429 (22.7%) ES proteins using Gene Ontology (GO) terms, 672 (35.5%) proteins to protein domains and established pathway associations for 223 (11.8%) sequences using Kyoto Encyclopaedia of Genes and Genomes (KEGG). The 162 (8.5%) ES proteins were also mapped to several important plant cell-wall degrading CAZyme families including chitinase, cellulase, xylanase, pectate lyase and endo -β-1, 4-xylanase. Our comprehensive analysis of M. incognita secretome provides functional information for further experimental study.